2021
DOI: 10.3389/fneur.2021.706639
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Attachment Style and Social Support in Patients With Severe Migraine. Applications in Doctor-Patient Relationships and Treatment Adherence

Abstract: Objectives: The aim of this observational study was to describe social support and patterns of attachment among patients with migraine. We hypothesized that in comparison to the general population, insecure attachment is overrepresented in migraine patients, and that these patients have less social support. We also aimed to study the specific relationship between attachment and social support. We hypothesized that patients with an insecure attachment style have less social support than patients with a secure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
5
1
Order By: Relevance
“…By contrast, it has been shown that headache sufferers had slightly more social support from their families than non-headaches sufferers [75]. Hence, it is di cult to draw de nitive conclusions given the heterogeneity of the clinic populations [70][71][72][73]75]. However, our results suggest that CM + MO patients place importance on tangible support from their family members, although they do not feel much satis ed with the support received from social networks [70,76,77].…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…By contrast, it has been shown that headache sufferers had slightly more social support from their families than non-headaches sufferers [75]. Hence, it is di cult to draw de nitive conclusions given the heterogeneity of the clinic populations [70][71][72][73]75]. However, our results suggest that CM + MO patients place importance on tangible support from their family members, although they do not feel much satis ed with the support received from social networks [70,76,77].…”
Section: Discussioncontrasting
confidence: 56%
“…The topic of social relationships in migraine is much debated. There is evidence reporting that migraine patients are less satis ed with social support than the general population [70][71][72]. Belot [72] found that patients with severe migraine judged the social support they received worse than the general population did.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although online relationships are generally a poor substitute for the possible benefits gained from physical relationships, online discussions about chronic illness with other patients may provide better support and resources that are then crucial to restore patient self-esteem, personal identity, and self-advocacy ( 28 ). Belot et al ( 27 ) reported that migraineurs were more likely to have an insecure attachment style, fewer people included in their social networks, and less satisfaction obtained from social connections than the general population; therefore, successful chronic pain management requires coping skills to navigate the emotional trauma of chronic pain and reduce the risk of mental illness.…”
Section: Medication Overuse Headache and Mental Healthmentioning
confidence: 99%
“…There are other aspects of social aging that are reported to be associated with migraine. It was hypothesized that insecure attachment was overexpressed in migraine patients and these patients had less social support as compared with general population [ 63 ]. This hypothesis was verified in a study with 101 consecutive patients evaluated with a battery of tests and questionnaires.…”
Section: Social Agingmentioning
confidence: 99%